2018
DOI: 10.1007/s12350-016-0623-z
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of abdominal belt for restricting respiratory cardiac motion and improving image quality in myocardial perfusion PET

Abstract: The belt technique restricts LV respiratory motion and improves the image quality of myocardial PET/CT, and it is well tolerated by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Respiratory and cardiac motion correction methods in PET have been investigated in the past [ 6 ], [ 7 ]. External motion tracking markers or sensors have been used in some studies [ 5 ], [ 8 ] to track respiratory motion at a high temporal resolution. Electrocardiography (ECG) is still the gold-standard when it comes to track the cardiac motion due to high temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory and cardiac motion correction methods in PET have been investigated in the past [ 6 ], [ 7 ]. External motion tracking markers or sensors have been used in some studies [ 5 ], [ 8 ] to track respiratory motion at a high temporal resolution. Electrocardiography (ECG) is still the gold-standard when it comes to track the cardiac motion due to high temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilization devices have also been proposed to control or suppress respiratory and/or body motion during PET acquisitions. 88 In the context of cardiac perfusion studies, Ichikawa and colleagues 130 investigated the use of an abdominal belt worn by patients to suppress the extent of respiratory motion. They found that the belt system, which the study participants reported as being well tolerated, significantly reduced the motion of the heart due to respiration compared to free-breathing: 8 mm of motion compared to 12 mm, respectively.…”
Section: Breath-hold Techniques and Patient Immobilizationmentioning
confidence: 99%